Dissection of left iliac artery during anterior lumbar interspace fusion: Report of a case. (April 2015) - Fischer, Uwe M; Davies, Mark G; Sayed, Hosam El
Vascular injury is an uncommon complication of spine surgery. Among the different approaches, anterior lumbar interbody fusion has increased potential for vascular injuries, since the great vessels and their branches overly the disc spaces to be operated on, and retraction of these vessels is necessary to gain adequate surgical exposure. The reported incidence for anterior lumbar interbody fusion-associated vascular injuries ranges from 0% to 18.1%, with venous laceration as the most common type. We report a case of anterior lumbar interbody fusion-associated left common iliac artery dissection leading to delayed acute limb ischemia developing in early post-operative period.